Central Mucoepidermoid Carcinoma - P. Andrle; L. Hauer; L. Hostička; D. Hrušák; J. Jambura; P. Pošta; A. Skálová (Czech Dental Chamber, 2013)
Introduction: Intraosseous mucoepidermoid carcinoma is a relatively rare variant of the histologically identical malignant tumor affecting salivary glands. It is a recently described separate nosological entity with a clearly defined histopathological feature. To date, only hundreds of cases of this disease have been reported in the literature worldwide. According to its typical occurrence this tumor is classified as a primary intraosseous carcinoma of the jaw. Methods: In the present paper, the authors describe two patients with this diagnosis, in both cases with tumors afflicting upper jaw diagnosed and treated at the Department of maxillofacial surgery in Pilsen since the years 2008. The treatment outcomes are evaluated after five-year follow-up. Results: The first patient was treated by the radical surgical procedure and adjuvant cancer therapy. Long-term complete remission was achieved and today the patient is with no evidence of malignant disease. The second patient is of advanced age and with much co-morbidity. For this reason, only radiotherapy was indicated, but without any therapeutic response in terms of tumor regression. The subsequently indicated palliative chemotherapy led to the significant tumor shrinkage. Currently, the patient is in the partial remission of malignant disease, with no evidence of tumor progression or metastases. Conclusion: The pathogenesis of intraosseous mucoepidermoid carcinoma is still not well understood. The diagnosis is based on histological examination performed by experienced pathologist. Immunohistochemical examination seems to be of no benefit for the diagnosis. A squamous cell carcinoma and glandular odontogenic cyst is necessary to be considered in histopathological differential diagnosis. A clinician has to rule out metastasis of salivary mucoepidermoid carcinoma in the jaws. Most intraosseous mucoepidermoid carcinomas are classified as low-grade tumors with the little metastatic potential. The radical resection procedure should be the first choice for the treatment of this cancer. Radiotherapy and chemotherapy are only indicated as an adjuvant therapy, especially in high-grade tumors. Despite its clear malignant nature the intraosseous mucoepidermoid carcinoma is not an aggressive tumor with high mortality.